The Camping Holidays Ladybird reader Level 2 - Sorrel Pitts; series editor 2021; Sorrel Pitts; text adoptor 2021; Naomi Rainbow; activities writer 2021; Wardour Studio; songs lyrics 2021 (UK Penguin Random House, 2021)
Twilight Sparkle and her friends go on a camping holiday. Everyone is excited! But camping isn$1 (Bt easy for all ponies. Rarity wants to stay clean, and Rainbow Dash wants everything to be fast and fun. When a problem happens, the ponies must work together to make the holiday a success.s
The series includes traditional tales, popular characters, modern stories, and non-fiction. Beautifully illustrated and carefully written by language learning experts, the series combines the best of Ladybird content with the structured language progression that will help children develop their reading, writing, speaking, listening and critical thinking skills.
Shelving location: M6
Ladybird Readers is an ELT graded reader series for children aged 3-11 learning English as a foreign or second language. The Camping Holiday, a Level 2 Reader, is A1 in the CEFR framework and includes practice for the Cambridge English A1 Movers tests. Short sentences contain a maximum of two clauses, introducing the past tense and some simple adverbs. The ponies go camping for the weekend. Bugs come to their camp, so the ponies go into a cave! Scootaloo doesn't like the cave.
Keywords: Cambridge English test practice